2013
DOI: 10.3892/ijo.2013.1815
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin-2 is associated with radioresistance in oral cancer and lung cancer cells

Abstract: The aim of the present study was to identify a target molecule that could predict the efficacy of radiotherapy in oral squamous cell carcinoma (OSCC). We used DNA microarray analysis to identify differences in gene expression after X-ray irradiation. We compared the gene expression profiles between X-ray (8 Gy)-irradiated Ca9-22 cells (an OSCC-derived cell line) and unirradiated Ca9-22 cells. A total of 167 genes with a 2-fold higher level of expression induced by X-ray irradiation were identified. Lipocalin-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Lipocalin 2 has been identified as a stress protein that is released in a variety of other sterile inflammatory conditions such as adipose obesity-related inflammation [20] and cancer. Recently, it has been reported that Lipocalin 2 is associated with radioresistance in oral cancer and lung cancer cells [21], and erlotinib resistance in NSCLC [22]. Functionally, Lipocalin 2 has been suggested in promoting tumorigenesis through enhancing tumor cell survival and proliferation, and metastatic potential [2325].…”
Section: Discussionmentioning
confidence: 99%
“…Lipocalin 2 has been identified as a stress protein that is released in a variety of other sterile inflammatory conditions such as adipose obesity-related inflammation [20] and cancer. Recently, it has been reported that Lipocalin 2 is associated with radioresistance in oral cancer and lung cancer cells [21], and erlotinib resistance in NSCLC [22]. Functionally, Lipocalin 2 has been suggested in promoting tumorigenesis through enhancing tumor cell survival and proliferation, and metastatic potential [2325].…”
Section: Discussionmentioning
confidence: 99%
“…Many transcription factors, including the estrogen and androgen receptors, regulate NGAL expression by both positive and negative mechanisms [67][68][69][70][71][72][73][74][75][76][77]. 11 NGAL is an important molecule in many different types of cancer including: breast [9,10,77], colorectal (CRC) [78,79], endometrial [80], esophageal [7,81], gastric cancer [6], liver [82][83][84], lung [85][86][87] ovarian [88], pancreatic [89,90], prostate [76,91], renal [8,92] and thyroid cancer [68]. In general, elevated NGAL expression has been associated with advanced cancer and poor prognosis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…When expression of NGAL was knocked down with small interfering RNA (siRNA), the sensitivity of the oral cancer Ca9-22 and HSC-2 cells to radiation was increased. The authors have suggested that NGAL expression may be used to predict radioresistance[85].The expression of NGAL was detected in 58/78 (76.3%) lung cancers and 4/30 (13.3%) adjacent tissues indicating that NGAL expression was more present in cancerous than non-cancerous adjacent tissues. The mechanisms of invasion in A549 lung cancer cells and the role of NGAL expression were examined.…”
mentioning
confidence: 97%
“…Lipocalin-2 (LCN2), which is a member of the lipocalin family and functions to ligate ferric siderophore-like molecules, is involved in various cancers including lung cancer (Shiiba et al, 2013 ), breast cancer (Yang et al, 2013 ), ovarian cancer (Cho and Kim, 2009 ), colon cancer and pancreatic cancer (Mannelqvist et al, 2012 ). The elevated levels of LCN2 tightly associate with the malignance and metastasis of cancer cells (Leng et al, 2009 ; Yang et al, 2009 ).…”
Section: Iron Is Implicated In a Variety Of Cancer Typesmentioning
confidence: 99%